Detection of left coronary ostial obstruction during transcatheter aortic valve replacement by coronary flow velocity measurement in the left main trunk by intraoperative transesophageal echocardiography. Issue 1 (January 2023) - Nomura, Takehiro; Teruo, Inoue; Miyasaka, Masaki; Hirose, Suguru; Enta, Yusuke; Ishii, Kazunori; Nakashima, Masaki; Saigan, Makoto; Toki, Yusuke; Sakurai, Mie; Munehisa, Yoshiko; Hata, Masaki; et al.
Abstract: Background: Coronary obstruction is a rare but catastrophic complication of transcatheter aortic valve replacement (TAVR) and occurs mostly at the left coronary artery (LCA) ostium. However, some patients do not show any clinical findings, and thus, its detection is sometimes difficult. The peak diastolic flow velocity in left main coronary artery (LM) was reportedly increased in significant stenosis lesions. We evaluated the effectiveness of measuring blood flow velocities in LM by transesophageal echocardiography (TEE) for the detection of LCA ostial obstruction during a TAVR procedure. Methods: A total of 1105 consecutive patients who underwent TAVR in Sendai Kousei Hospital between September 2014 and December 2020 were enrolled. The LM blood flow velocity was measured at pre- and post-valve implantation. Results: Among the 1105 patients, 9 had LCA ostial obstruction. The peak LM blood flow velocity at post-TAVR [0.90 (0.39–1.15) vs. 0.37 (0.28–0.50) m/s; p  = 0.0046) was significantly higher in 9 patients who had LCA ostial obstruction, compared with the remaining 1096 patients who had not (controls), although no significant difference was observed before the TAVR procedures between the two groups. The post- to pre-TAVR LM flow velocity ratio [2.26 (1.31–3.42) vs. 1.06 (0.82–1.36); p  = 0.0030] was also significantly higher in patients with LCA obstruction, compared to the controls. Furthermore, the post- to pre-TAVR LM blood flow velocity ratio was >2.0 in all six hemodynamically stable patients with LCA obstruction, whereas <2.0 in all three patients with LCA obstruction who showed hemodynamic collapse at post-TAVR procedure. Conclusion: Coronary blood flow velocity in LM significantly increased in hemodynamically stable LCA obstruction patients. The intraprocedural TEE measurement of the LM flow velocities would be potentially useful to detect asymptomatic and hemodynamically stable LCA ostial obstruction. Graphical abstract: Unlabelled Image Highlights: Left coronary artery (LCA) obstruction is an often hard-to-detect transcatheter aortic valve replacement (TAVR) complication. The flow velocity in left main trunk were measured by transesophageal echocardiography before and after valve implantation. The blood flow accelerated in the LCA obstruction patients after valve implantation. The post/pre-TAVR velocity ratios were >2.0 in all stable LCA obstruction patients. The intraprocedural measurement of flow velocity is useful for detecting LCA obstruction.